Improving Lesson Plan Models Using Online-Based in the New Normal Era - Firman Edi; Ambiyar Ambiyar; Unung Verawardina; Samsir Samsir; Ronal Watrianthos (EDUTEC : Journal of Education And Technology, 2021)
The COVID-19 pandemic has changed human life dramatically. The new pushes digital technology to become part of the educational system at an accelerated level of growth. This study is meant to build a model of an online-based lesson plan as a learning development in the new normal era. The research method uses a descriptive comparison by observation, interviews, and literature analyses. Results have demonstrated that the development of an online learning plan model for learning tools leads to the needs of potential learning systems. The challenges encountered include the lack of capability of human resources to operate online tools, the limited technology, and the challenge of adapting learning tools to the objectives of the curriculum. The online learning planning model can be applied with the assistance of the government, schools, and teachers.